Gerakan Buka Kelas with the Assistance of Nearpod Platform in Astronomy and Geophysics Courses - Susanti, Nova (Indonesian Research Journal in Education |IRJE|, 2023)
This research aimed to provide information about students' perceptions of the Nearpod’s use in Astronomy and Geophysics courses. The research site was the PMIPA Physics Education study program, FKIP, Universitas Jambi. Furthermore, the research samples were the bachelor's degree students who took Astronomy and Geophysics courses. The research was conducted using the stages that apply in lesson study activities. The research implementation took place in 2 cycles which were adjusted to the allocation and selected subject. Each cycle consists of the stages of the plan, do, and see. The instrument used in this research was the Nearpod usage perception instrument. Collecting student perception data using Google Forms while the learning process was using video recordings of learning, student perception data were analyzed using Excel.